Nature and characteristics of after pain among postnatal mothers admitted in a tertiary care hospital in South India - Namboothiri, Smitha P.; iswanath, Lekha V (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: All postnatal mothers experience pain in some form or the another. Crampy pain in the abdomen known as after pain is a determinant of the uterine involution which is more evident clinically in the first four days postpartum. The present study emerged with a view to study the nature and characteristics of after pain among postnatal mothers at a tertiary care hospital in South India. Methods: A prospective survey design was used for the study. Quota sampling was used to select 100 postnatal mothers, 50 mothers who had caesarean section and 50 mothers who had vaginal delivery. The mothers were enrolled for the study consecutively in 12-24 hours postpartum till the required sample size was obtained in both the groups. A demographic proforma was designed to collect the background information. The characteristics of after pain were assessed using numerical pain rating scale every 24 hours in the first three postpartum days. Results: The mean scores of pain on the first three postpartum days among mothers after vaginal delivery were 2.84, 2.1 and 0.84 respectively and for mothers after caesarean section were 1.6, 1.66 and 0.74 respectively. The scores were greatest on the first postpartum day. No association was found between after pain and variables like mode of delivery and age of the mother. It was found that after pain had an association with with parity on the first and third postpartum days. Conclusions: Since after pain is an indicator of uterine involution, strict protocols should be established in maternity care units for a comprehensive assessment of after pain.